Bioinspired, Omnidirectional, and Hypersensitive Flexible Strain Sensors. Issue 17 (24th March 2022) - Liu, Linpeng; Niu, Shichao; Zhang, Junqiu; Mu, Zhengzhi; Li, Jing; Li, Bo; Meng, Xiancun; Zhang, Changchao; Wang, Yueqiao; Hou, Tao; Han, Zhiwu; Yang, Shu; et al.
Abstract: Sensors are widely used in various fields, among which flexible strain sensors that can sense minuscule mechanical signals and are easy to adapt to many irregular surfaces are attractive for structure health monitoring, early detection, and failure prevention in humans, machines, or buildings. In practical applications, subtle and abnormal vibrations generated from any direction are highly desired to detect and even orientate their directions initially to eliminate potential hazards. However, it is challenging for flexible strain sensors to achieve hypersensitivity and omnidirectionality simultaneously due to the restrictions of many materials with anisotropic mechanical/electrical properties and some micro/nanostructures they employed. Herein, it is revealed that the vision‐degraded scorpion detects subtle vibrations spatially and omnidirectionally using a slit sensillum with fan‐shaped grooves. A bioinspired flexible strain sensor consisting of curved microgrooves arranged around a central circle is devised, exhibiting an unprecedented gauge factor of over 18 000 and stability over 7000 cycles. It can sense and recognize vibrations of diverse input waveforms at different locations, bouncing behaviors of a free‐falling bead, and human wrist pulses regardless of sensor installation angles. The geometric designs can be translated to other material systems for potential applications including human health monitoring and engineering failure detection. Abstract : Based on the ultrasensitive and omnidirectional sensing function of scorpions to weak vibration signals, the biological mechanism is explored and a flexible strain sensor inspired by the slit sensillum embedded on the walking legs of scorpions is fabricated. Results demonstrate that the sensors also have hypersensitive, omnidirectional sensing, and direction discrimination to vibration stimuli, similar to that of scorpions.